An Advanced Human-Robot Interaction Interface for Teaching Collaborative Robots New Assembly Tasks - Papadopoulos, Christos; Mariolis, Ioannis; Topalidou-Kyniazopoulou, Angeliki; Piperagkas, Grigorios; Ioannidis, Dimosthenis; Tzovaras, Dimitrios (Interactive Collaborative Robotics, 2017)
This paper presents an advanced human-robot interaction (HRI) interface that allows teaching new assembly tasks to collaborative robots. The interface provides the proper tools for a non-expert user to teach a robot a new assembly task in a short amount of time through advanced perception and simulation technologies. The assembly is demonstrated by the user through an RGBD camera and the system extracts the needed information for the assembly to be simulated and performed by the robot, while the user guides the process. The HRI interface is integrated with the ROS framework and is built as a web application that can be operated through a PC tablet. We evaluate the interface with user experience rating from test subjects that are requested to teach an assembly to the robot.